Preductal Hemodynamic Redistribution in Preterm Infants with Patent Ductus Arteriosus - Aimann Surak (Case Reports in Pediatrics)
A patent ductus arteriosus is a common entity in preterm infants. Literature is lacking regarding physiological effects on preductal circulation. This report describes 3 patients with abnormal flow Doppler pattern in brachiocephalic artery. Further research is warranted to better understand the impact of PDA on preductal circulation.